IMPLEMENTASI AKAD DALAM PERBANKAN SYARIAH DI INDONESIA: STUDI LITERATUR TERHADAP PRINSIP MURABAHAH, MUDHARABAH, DAN MUSYARAKAH (An Nawawi, 2025)
Islamic banking in Indonesia has experienced significant growth over the past two decades, marked by increasing assets, customer numbers, and product diversification. This study aims to analyze the implementation of the main contracts (akad) in Islamic banking, specifically murabahah, mudharabah, and musyarakah, through a literature review of various Islamic legal sources, Indonesian Islamic banking regulations, and previous empirical research. The method employed is library research with a descriptive qualitative approach through content analysis of primary and secondary sources. The findings indicate that murabahah contracts still dominate Islamic banking financing portfolios due to their relatively low risk and income certainty, while mudharabah and musyarakah contracts hold great potential in driving the real sector but remain constrained by moral hazard, asymmetric information, and human resource limitations. This study recommends strengthening sharia governance, improving public literacy, and leveraging financial technology to optimize the application of profit-sharing-based contracts.
Keywords: sharia contracts; Islamic banking; murabahah; mudharabah; musyarakah; literature review